Study on the profile of deaths from external causes in the state of Piaui (Research, Society and Development, 2023)
Objective: to analyze deaths from external causes in the State of Piauí, from 2009 to 2019. Methodology: this is a quantitative, epidemiological, documental, descriptive, exploratory, retrospective and cross-sectional study, carried out by consulting the System of Information on Mortality (SIM), of the Department of Informatics of the SUS (DATASUS). At the same time, a sociodemographic form was applied, with the following variables: sex, age group, color/race, marital status, education and place of death. Results: the highest number of deaths from external causes occurred in males, accounting for 87.4% of the 24,435 cases. It was also seen a predominance of the age group from 20 to 29 years old, with 25.8% of the total, followed by adults from 30 to 39 years old, with 20.2%. In the same period, the lowest rates of mortality from external causes occurred in the extremes of age, that is, in children under 14 years old, with 3.9% and in adults aged 70 to 79 years old, with 4.8% of the total number of deaths. Conclusion: the results show that deaths from external causes occurred more frequently in male patients aged between 20 and 29 years, single, with low education. Thus, the importance of studies based on the analysis and interpretation of vital statistics is highlighted, since from such data, the State can outline public policies for the reduction of mortality rates, since, in addition to the burden caused by the assistance provided, there are losses of economically active population.